Effect of alternating combination chemotherapy consisting of cyclophosphamide, doxorubicin, vincristine, cisplatin, and etoposide for small cell lung cancer on hematopoietic progenitors in the peripheral blood. - Shimizu, E. (Nature Publishing Group, 1993)
The effects of a combination chemotherapy (CAV-PVP) consisting of cyclophosphamide, doxorubicin, hydrochloride (dox) and vincristine (CAV) alternating with cisplatin and etoposide (PVP) on peripheral blood hematopoietic progenitor cells (PBHPs) were studied in five patients with small cell lung cancer (SCLC). The kinetics of the CFU-GM levels were different during the CAV and PVP phases. None of the five patients displayed a rebound increase in the level of peripheral blood CFU-GM during the CAV phase. In contrast, all five patients displayed a rebound increase in peripheral blood CFU-GM levels during the PVP phase of the alternative combination chemotherapy (3-5 weeks after the initiation of PVP regimen). These findings indicate the optimal timing for leukapheresis to obtain PBHPs in SCLC patients which have been treated with an alternating combination chemotherapy consisting of CAV-PVP.